2003
DOI: 10.1002/cncr.11526
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in pathologic and clinical lymph node staging in oral tongue carcinoma

Abstract: At present, storage capacities of single tank and tank farm have been greatly increasing. This change poses a real challenge for the applicability of current design standards. This article focuses on the applicability of safety spacing between tanks, which is one of the most important parameters of tank farm safety design. Taking PHAST and FDS as main research tools, the consequences of representative accidental scenarios were evaluated for different sizes of oil tanks to study the safety performance change ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
119
2
12

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 166 publications
(137 citation statements)
references
References 60 publications
4
119
2
12
Order By: Relevance
“…No randomised controlled trials have yet been performed to compare the effectiveness of surgery with chemoradiation, and the usefulness of chemoradiation therapy involving systemic chemotherapy thus remains to be clarified. After surgery, the 5-year survival rate ranged from 27 to 60% of stage III patients, while it ranged from approximately 12 to 40% of stage IV patients (Chen et al, 1999;Sessions et al, 2002;Greenberg et al, 2003;Lo et al, 2003;Gorsky et al, 2004;Liao et al, 2006;Fan et al, 2007); our results were therefore similar to the results after surgery. In particular, the results of arterial injection therapy by cisplatin with sodium thiosulphate were excellent.…”
Section: Discussionsupporting
confidence: 80%
“…No randomised controlled trials have yet been performed to compare the effectiveness of surgery with chemoradiation, and the usefulness of chemoradiation therapy involving systemic chemotherapy thus remains to be clarified. After surgery, the 5-year survival rate ranged from 27 to 60% of stage III patients, while it ranged from approximately 12 to 40% of stage IV patients (Chen et al, 1999;Sessions et al, 2002;Greenberg et al, 2003;Lo et al, 2003;Gorsky et al, 2004;Liao et al, 2006;Fan et al, 2007); our results were therefore similar to the results after surgery. In particular, the results of arterial injection therapy by cisplatin with sodium thiosulphate were excellent.…”
Section: Discussionsupporting
confidence: 80%
“…2) have variable incidence and are widely accepted as one of the major prognostic factors in patients with OSCC. [32][33][34][35] Their presence is associated with a decrease in global survival to roughly half as well as with higher recurrence rates. 24,[34][35][36] Cervical node metastases may be classified into 2 distinct categories: overt (clinical) or nonovert (occult).…”
Section: Review Of the Literature Patient-related Factorsmentioning
confidence: 99%
“…36 A retrospective study involving 266 patients who had previously undergone surgery and cervical node dissection, revealed that 34% of those initially classified as cN0 had, in fact, occult metastatic disease (pN1). 33 Therefore, staging based on pathologic analysis following neck dissection should be considered, in order to identify high-risk patients who may benefit from adjuvant therapy, because those with node metastases show significantly lower survival rates than those with disease-free nodes. 33,34 Tumor thickness.…”
Section: Review Of the Literature Patient-related Factorsmentioning
confidence: 99%
See 2 more Smart Citations